Optical solitons in negative-index meta-materials - U. A., Mofiz (© 2013 IEEE, 2016)
This conference paper was presented in the 2nd International Conference on Advances in Electrical Engineering, ICAEE 2013; Dhaka; Bangladesh; 19 December 2013 through 21 December 2013 [© 2013 IEEE]. The conference paper's definite version is available at: http:doi.org/10.1109/ICAEE.2013.6750301